Teachers' Strategy to Improve Learners' Comprehension in Islamic Education in Elemantary School - Nasril Nasril; Hilda Nofrianti; Mukhtia Sari; Firda Khairati Amris; Burhanuddin Burhanuddin (Islamic Studies and Development Center in Collaboration With Students' Research Center Universitas Negeri Padang, 2023)
This study aims to find out how the strategy is to increase students' understanding in learning Islamic religious education in elementary schools. This study used a qualitative method with a case study approach. The data source was taken through in-depth interviews with ten Islamic religious education teachers in several elementary schools. All data were analyzed thematically with techniquesInteractive Analysis Model Miles & Huberman. Research findings found four strategies for teachers in improving student understanding of the nature of Islamic religious education learning. The four strategies are i) wheezingIntegrate technology as a learning medium so that students can easily understand the material, ii) condition students to study in groups, so that collaboration among students is formed in learning, iii) Provide rest periods in learning sessions to overcome learning saturation, iv) Varying learning methods such as singing and carry out games in conveying subject matter. The research findings also found that the four strategies used by the teacher were implemented well and even succeeded in increasing students' understanding in understanding the subject matter. These four strategies can be used as examples for Islamic religious education teachers in various elementary schools in carrying out learning.